1993
DOI: 10.1103/physreva.48.1604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atomic coherences in the Jaynes-Cummings model: Photon statistics and entropy

Abstract: The Mandel Q factor, antibunching efFect, and entropy are calculated for the Jaynes-Cummings model with the atom being initially in a coherent superposition of the upper and lower states. The value of Mandel's Q factor in the collapse region is found and compared with the behavior of the field entropy. PACS number(s): 42.50.Dv, 03.65.w, 42.52. +x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In ®gure 2 we have plotted the time evolution of the ®eld phase ¬…t †, computed numerically from the exact solution (17). We can see that this phase is almost a linear function, with small superimposed oscillations that can be noticed only for small values of n 0 : the greater n 0 , the smaller the growth of ¬…t †.…”
Section: Field Dynamics and Rabi Oscillationsmentioning
confidence: 94%
See 1 more Smart Citation
“…In ®gure 2 we have plotted the time evolution of the ®eld phase ¬…t †, computed numerically from the exact solution (17). We can see that this phase is almost a linear function, with small superimposed oscillations that can be noticed only for small values of n 0 : the greater n 0 , the smaller the growth of ¬…t †.…”
Section: Field Dynamics and Rabi Oscillationsmentioning
confidence: 94%
“…Considerable attention has been paid to the statistical properties of the ®eld in the JCM [16,17]. However, given the di erent treatment of the ®eld variables, in order to compare the semiclassical and quantum versions of the model, it seems more appropriate to focus on the behaviour of atomic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (15) shows that if the atom is initially fully excited (de-excited), it will be forms Pfi(0) = I Pn,m(0 )In)(mI, (8) and n, m Pat = ( Pee Pe g (9) Pg , Pgg switched down (up) at times t42k>, but remains in a pure state . For other initial atomic states, the atom becomes completely mixed at these times .…”
Section: Paafi) = Tr Fi(at)p(t) = Tr Fi(at)[u+ (T)pat(0)pfi(0) U(t)]mentioning
confidence: 99%
“…Using the entropy concepts, Orszag, Retamal, and Saavedra have pointed out that the pure atomic state can be generated even from the initially mixed ones [7] . In [8] we have also shown that the entropy may give a better understanding of the evolution of the field statistics .…”
Section: Introductionmentioning
confidence: 94%
“…Singh [9] studied antibunching in resonance fluorescence in both stationary and transient nonstationary regimes. Dung et al [10] and Aliskenderov et al [11] analysed the non-stationary-field antibunching effects in the Jaynes-Cummings model, whereas Feng et al [12] studied the photon-antibunching effects in the model of light propagation through a nonlinear fibre with gain.…”
Section: Introductionmentioning
confidence: 99%